Field reports, Iowa Bird Life, fall 1999, Lee Schoenewe - Schoenewe, Lee A.et al (1999)
An annotated list of birds sighted by Lee Schoenewe. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1999. Epson - sheet feed